Review Procedures of Transport Vehicles in KMP Baronang Track Bastiong - Sofifi North Maluku Province - Chairul Insani Ilham; Damaida Hatina; Devi Octa Saputri (IWTJ : International Water Transport Journal, 2019)
Bastiong Ferry Port is managed by PT. ASDP Indonesia Ferry (Persero) Branch of Ternate airport 9 and examined by eight types of ferry Ro-Ro (Roll on-Roll off). The commercial track located in The Port of Bastiong Ferries is the track of Bastiong - Sofifi which the shipping distance is 14 nautical miles and has a travel time of 2 hours with average speed - average 8 knots. The Tracks Bastiong - Sofifi has the highest trip which is 7 trips a day, therefore it is allowed that the passengers and vehicles that transported more than other tracks. So much in ordinances of transport does not comply with the regulation No. 115 of 2016 which includes: weighing before loading onto ships, information on the weight and type of content, the type of fastener tools in use, the distance between the vehicle and the sterilization space vehicles of passengers during the voyage. Based on analysis of the problems in the KMP. Baronang, still found some problems such as the unavailability of the weighbridge at The Port of Bastiong Ferries, information about the weight and type of cargo that is not attached when the vehicle is loaded onto the ship, the type of fastener tools that are not in accordance with the rules that have been set, the distance between the vehicle distance adjacent vessel and the condition of the vehicle is not sterile space of the passengers during the voyage. Therefore, it is necessary in a further analysis concerning the procedures for the transport to suit the regulation No. 115 of 2016 ship that security and safety is maintained during the voyage.